The protective effects of sesamol and/or the probiotic, Lactobacillus rhamnosus, against aluminum chloride-induced neurotoxicity and hepatotoxicity in rats: Modulation of Wnt/β-catenin/GSK-3β, JAK-2/STAT-3, PPAR-γ, inflammatory, and apoptotic pathways - Abu-Elfotuh, Karema; Selim, Heba Mohammed Refat M.; Riad, Omnia Karem M.; Hamdan, Ahmed M. E.; Hassanin, Soha Osama; Sharif, Asmaa F.; Moustafa, Nouran Magdy; Gowifel, Ayah M.H.; Mohamed, Marwa Y. A.; Atwa, Ahmed M.; Zaghlool, Sameh S.; El-Din, Mahmoud Nour (Frontiers in Pharmacology, 2023)
Aluminium (Al) is accumulated in the brain causing neurotoxicity and neurodegenerative disease like Alzheimer’s disease (AD), multiple sclerosis, autism and epilepsy. Hence, attenuation of Al-induced neurotoxicity has become a “hot topic” in looking for an intervention that slow down the progression of neurodegenerative diseases. Our study aims to introduce a new strategy for hampering aluminum chloride (AlCl3)-induced neurotoxicity using a combination of sesamol with the probiotic bacteria; Lactobacillus rhamnosus (L. rhamnosus) and also to test their possible ameliorative effects on AlCl3-induced hepatotoxicity. Sprague-Dawley male rats were randomly divided into five groups (n=10/group) which are control, AlCl3, AlCl3+Sesamol, AlCl3+L. rhamnosus and AlCl3+Sesamol+L. rhamnosus. We surveilled the behavioral, biochemical, and histopathological alterations centrally in the brain and peripherally in liver. This work revealed that the combined therapy of sesamol and L. rhamnosus produced marked reduction in brain amyloid-β, p-Tau, GSK-3β, inflammatory and apoptotic biomarkers, along with marked elevation in brain free β-catenin and Wnt3a, compared to AlCl3-intoxicated rats. Also, the combined therapy exerted pronounced reduction in hepatic expressions of JAK-2/STAT-3, inflammatory (TNF-α, IL-6, NF-κB), fibrotic (MMP-2, TIMP-1, α-SMA) and apoptotic markers, (caspase-3), together with marked elevation in hepatic PPAR-γ expression, compared to AlCl3-intoxicated rats. Behavioral and histopathological assessments substantiated the efficiency of this combined regimen in halting the effect of neurotoxicity. Probiotics can be used as an add-on therapy with sesamol ameliorate AlCl3-mediated neurotoxicity and hepatotoxicity.